Increasing Firm Value Based On External Governance And Modern Finance theory - Ibnu Khajar; Ahmad Hijri Alfian (Journal of Business and Management Review, 2022)
It is based on the theory of firm and external agency that through investment, funding, and dividend decisions to achieve max firm value. The purpose of this study is to re-examine this model for cases in Indonesia. The sample population of this study comprised 18 companies listed on the Indonesia stock exchange that become the members of LQ-45 index from 2016-2019. The samples were selected by purposive sampling. This study used panel data regression analysis program with Eviews-9 application to answer the research objectives. The results indicated that investment decisions had a significant positive effect, funding decisions had a significant negative effect and dividend decisions had no significant negative effect on firm value.